Dissipation of pore pressure during one dimensional consolidation of an artificial marine clay - Tsai, Ching-ta; Brand, E.W.; Moh, Za-Chieh; Nelson, John D.; Government of the Republic of China (Bangkok : Asian Institute of Technology, 1972)
Pore pressure dissipations during one-dimensional consolidation of an artificial marine clay were studied. The load increment ratio was varied from 0.25 to 4.0, while the load increment durations used were 24 hours and 48 hours. It was found that the rate of pore pressure dissipation was function of load increment ratio, as predicted theoretically by BARDEN & BERRY (1965), DAVIS & RAYMOND (1965) and SIMONS & TAN (1969), the smaller the load increment ratio, the faster the rate of pore pressure dissipation. The available theories, however3 did not generally predict the pore pressures very well and it was concluded that Terzaghi's theory might as well be used for all loading conditions. The measured effect of load increment duration on the rate of pore pressure dissipation was insignificant. An attempt was made to estimate coefficients of consolidation from rates of pore pressure dissipation and these were compared with those obtained in the conventional way from the compression time curves.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1972
Keywords: Soil consolidation; Clay